Content curation on virtual environments: a perspective from the university profesor - Hernández-Campillo, Thais Raquel; Carvajal Hernández, Bárbara María; Legañoa Ferrá, María de los Ángeles; Campillo Torres, Irima (Apertura : revista de innovación educative, 2022)
The objective of this paper was to characterize the current state of content curation in university professors. Also, a diagnosis was made to establish the informational competencies that these professionals possessed. The study methodology was based on the quantitative perspective with a descriptive scope and the use of the survey as a research technique that evaluated four dimensions: search, selection, characterization and dissemination of digital content. The results presented a set of shortcomings in the explicit dimensions, with an emphasis on characterization, since in educational digital content the textual format prevailed and critical evaluations were scarce. Moreover, insufficient use of content curation tools was detected. A wider participation of subjects due to the social distancing caused by covid-19 was evidenced as a limitation. The novelty of the study consisted in analyzing content curation with an informational competence approach, transversal in the training of university professors. It was concluded that there is little training in relation to the curation of content for teaching, as some indications of informational performance were observed, in isolation that hindered a better preparation of the subject.